FORECASTING MIGRATION MOVEMENTS IN UKRAINE (INNOVATIVE ECONOMY, 2023)
Novosad I.Ya., Ruska R.V., Plaskon S.A. FORECASTING MIGRATION MOVEMENTS IN UKRAINEPurpose. The purpose of the article is to provide a well-founded analysis and forecasts of future migration events that can significantly affect the further development of Ukraine.Methodology of research. The following methods were used in the research process: analysis and synthesis – to study the object and subject of research; abstract and logical (theoretical generalizations and formulation of conclusions); modeling of the dynamics of time series of external migration of the population of Ukraine.Findings. During the assessment of the migration situation, it was established that it significantly affects the demographic level of the population, especially after February 24, 2022, when an active exodus of the population was observed. According to the UN, as of August 2023, 6.2 million refugees have already left Ukraine. However, according to information from the State Border Guard Service, the number of people who fled the war in Ukraine is 3.2-3.5 million, and there is a threat of a further increase in this number. By building models of future migration events, a projected migration balance was obtained, which shows an increase in the number of people leaving Ukraine. Thus, Ukraine is facing significant demographic losses, which complicates its economic existence and post-war recovery processes. The success of refugee return in the medium and long term depends to a large extent on the end of the armed conflict and the improvement of the social and economic component of society. Ensuring the conditions for the return of Ukrainians from abroad largely depends on effective systemic measures of state regulation.Originality. Peculiarities of migration processes have acquired further development. Mathematical toolkit made it possible to investigate and establish the intensity of population migration, which is caused not only by economic factors, but also by unforeseen circumstances.Practical value. The practical significance of this research work is that Ukraine is facing significant demographic losses, and the results of the study can be used to analyze and predict future migration events.Key words: population migration, migration factors, refugees, internally displaced persons (IDPs), Russian-Ukrainian war, time series, forecasting.
Keywords: population migration; migration factors; refugees; internally displaced persons (IDPs); Russian-Ukrainian war; time series; forecasting.